Analisis Kelayakan Usaha Budidaya Chlorella sp Skala Lab - Nelwida, Nelwida; Hariski, M.; Yunita, Lauura Hermala; Wulanda, Yoppie (Universitas Galuh, 2024)
Chlorella sp is a type of microalgae that performs photosynthesis with pigments and chlorophyll. Chlorella sp contains nutrients needed by fish farmers for natural feed in aquaculture ponds but is not widely known by fish farmers in Jambi even though cultivation is quite easy to do, has the potential to be developed at home and as additional income for farmers. The purpose of this study is to determine the feasibility of cultivating Chlorella sp on a lab scale before being applied on a home scale. This research was carried out at the Faculty of Animal Husbandry, Jambi University from May to August 2023. The quantitative descriptive method used in this study is a business feasibility study with NPV and BCR investment criteria. The results showed that the average NPV value was Rp. 4,426,380,- and the average BCR value was 1.30 this means that the lab-scale Chlorella sp cultivation business is included in the profitable and feasible category.